The cellular uptake and endosomal escape mechanisms of chitosan-protamine-siRNA nanoplexes for efficient gene transfection and silencing - EKENTOK ATICI, CEYDA; ÖZBAŞ, SUNA; CÖMEZ, BİRNUR (My University, 2021)
Aim: The use of antisense-based molecules in gene expression inhibition has allowed the design of a new pathway for therapeutics. In order to ensure that oligonucleotides with gene silencing potential can be used effectively in therapy, a suitable carrier system is required that can be transported to the target site. In this study, gene silencing activities of siRNA targeted to the LacZ gene were compared and the gene delivery capabilities, transfection efficiency, cellular uptake and endosomal escape mechanisms of nanoplexes prepared with siRNA and chitosan/protamine polymers were investigated. Material and methods: Nanoplex formulations were prepared by simple complexation method of chitosan/protamine polymers and oligonucleotides. The particle size and zeta potential of the prepared nanoplexes were measured, and their serum and enzyme stability were investigated. In order to determine the transfection and gene silencing activities of the selected formulations, HEK293 cells stably expressing beta-gal were prepared, inhibition of beta-gal protein was measured by enzymatic assay and suppression by X-gal method was evaluated microscopically. Cellular uptake and endosomal escape mechanisms of nanoplexes were studied. Results: Chitosan/Protamine/siLacZ nanoplexes have been observed to protect siRNA against enzymatic and serum degradation for up to 48 hours. It was observed that the transfection efficiency was the highest in the formulations prepared together with chitosan/protamine at a rate of 10/10/1. It was observed that the transfection increased significantly with the increase in the ratio of chitosan and protamine. Transfection efficiency was found to be 88.60% at a rate of 10/10/1. In the cellular uptake study, it was observed that the inhibitor that reduced cellular uptake the most was phenylarsine oxide, and the uptake of siRNA carried by nanoplexes was 56%. There was no decrease in cellular uptake when chlorpromazine hydrochloride inhibitor was administered. This indicated that the nanoplexes were not uptake by clathrin-mediated endocytosis. It was observed that cellular uptake was 75% with colchicine, this inhibitor decreases cellular uptake by inhibiting microtubules in cells. Conclusion: It has been shown that cellular uptake and transfection studies with chitosan/protamine nanoplexes can be used as an effective carrier system for siRNA transport.
Keywords: siRNA; LacZ; cellular uptake; chitosan; protamine; nanoplexes